EFEKTIVITAS PENGGUNAAN APLIKASI PEMBELAJARAN MATEMATIKA ANMATH UNTUK MENINGKATKAN LITERASI NUMERASI - Cahyani, Paramodyta Diah Ayu; Khuzaini, Nanang (FKIP Universitas Al Washliyah Medan, 2024)
The purpose of this study is to determine the effectiveness of using the ANMATH mathematics learning application in improving students' numeracy literacy. The type of research conducted is experimental research using a pretest-posttest control group design. The population used in this study consists of 11th-grade students at SMA Negeri 1 Sedayu. The sample used in this study includes students from class XI MIPA 1 and XI MIPA 2, selected through purposive sampling technique. Data collection techniques used include observation, interviews, and the administration of pretest and posttest questions to assess students' numeracy literacy on sequences and series material. The hypothesis of this study is that the use of the ANMATH mathematics learning application can enhance students' numeracy literacy more effectively than direct learning without using the ANMATH mathematics learning application. The results of this study indicate that the use of the ANMATH mathematics learning application, which includes numeracy literacy indicators, has been proven effective in improving students' numeracy literacy. This conclusion is based on statistical tests, namely the Paired Sample T-Test, where the test results from the experimental class and the control class have a sig. 2-tailed value < 0.05, the Independent Sample T-Test, which has a sig. 2-tailed value < 0.05, and the mean difference test showing an increase in the experimental and control classes of 39.94 and 19.28, respectively. These results demonstrate that learning using the ANMATH mathematics learning application is more effective in improving students' numeracy literacy compared to learning without using the ANMATH mathematics learning application.